A Concept of a Vision System for Position DeterminationUsing Spatial-Time-Frequency Analysis - MIŚ, Piotr; SZULIM, Przemysław; MĄCZAK, Jędrzej (Engineering Transactions, 2025)
This paper presents the concept of a vision system designed to determine the position of a camera within a given coordinate system. The system focuses on identifying pulsating light markers in images recorded by the camera. These markers are characterized by specific colors, pulsation frequencies and known locations. Detection is achieved using a spatial-time-frequency processing method developed by the authors. The identified markers serve as input data for a mathematical model that determines the camera’s position within the reference system. The article discusses the theoretical foundations of the proposed system design. The system was subjected to testing to verify its operational accuracy and precision in position determination. The results of these tests are presented. The article concludes with a summary of the work and a discussion of the system’s further development and practical applications.